Investering i spannmålstorkning och lagring på gårdsnivå - Westman, Karl-Erik (2006)
The current situation for Swedish grain farmers facing a situation with decreasing profitability makes it necessary for the farmers to find ways of increasing the margins in their grain growing. Decreasing profitabilities along with Lantmännens closing of grain elevators contribute to the necessity for farmers to invest in grain storing and drying at the farm. By investing in capacity for drying and storage of grain on the farm it is possible to recieve a higher price on the grain sold due to the possibility to sell when the price is higher compared to the harvesting season.